2001
DOI: 10.1192/bjp.179.4.290
|View full text |Cite
|
Sign up to set email alerts
|

Systematic meta-review of depot antipsychotic drugs for people with schizophrenia

Abstract: Depot antipsychotics are safe and effective. They may confer a small benefit over oral drugs on global outcome. Those for whom depots are most indicated may not be represented. Large studies are required to discern differences in relapse rates and long-term adverse effects, and data on satisfaction, quality of life and economics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
184
0
12

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 265 publications
(203 citation statements)
references
References 30 publications
7
184
0
12
Order By: Relevance
“…Meta-analytic review of first-generation depots found little difference between individual medications. 5 No direct comparisons of risperidone long-acting injection with the first-generation depots are available except for one open, 6-month randomised study that showed favourable outcome for risperidone long-acting injection compared with zuclopenthixol decanoate for individuals with comorbid substance misuse. 6 Due to the growing trend towards the use of second-generation antipsychotics in general, 7 including risperidone long-acting injection, despite the lack of head-to-head evidence noted above, we aimed to retrospectively identify and measure the outcome of patients started on: risperidone long-acting injection, zuclopenthixol decanoate, flupentixol decanoate, fluphenazine decanoate, pipothiazine palmitate and haloperidol decanoate.…”
mentioning
confidence: 99%
“…Meta-analytic review of first-generation depots found little difference between individual medications. 5 No direct comparisons of risperidone long-acting injection with the first-generation depots are available except for one open, 6-month randomised study that showed favourable outcome for risperidone long-acting injection compared with zuclopenthixol decanoate for individuals with comorbid substance misuse. 6 Due to the growing trend towards the use of second-generation antipsychotics in general, 7 including risperidone long-acting injection, despite the lack of head-to-head evidence noted above, we aimed to retrospectively identify and measure the outcome of patients started on: risperidone long-acting injection, zuclopenthixol decanoate, flupentixol decanoate, fluphenazine decanoate, pipothiazine palmitate and haloperidol decanoate.…”
mentioning
confidence: 99%
“…Quando pacientes com esquizofrenia consentem tomar a medicação, seja por via oral ou intramuscular, não se observa diferença quanto à eficácia terapêutica entre antipsicóticos de ação curta e prolongada (1)(2) . forma, este procedimento exige cuidado (6) .…”
Section: Indicação E Início Do Tratamentounclassified
“…Depot injections, in particular, have worked well to deliver antipsychotic medications over long periods of time with enhanced efficacy over oral dosing (Adams et al 2001;Gastpar et al 2005). However, limitations of depot formulations restrict more significant improvements in adherence and efficacy.…”
Section: Introductionmentioning
confidence: 99%